Causal links between plasma lipidome and ovarian cancer risk: evidence from Mendelian randomization - Huke Dong; Chen Zhang; Hua Wang; Ying Dai (Discover Oncology)
Abstract S. Plasma lipids in circulation are integral to the physiopathological processes of the ovary and may impact the development of various ovarian conditions, including ovarian cancer (OC). This study utilized a two-sample Mendelian randomization method to examine the causal link between changes in 179 plasma lipid groups and ovarian cancer (OC) to gain deeper insights into this association. We used the inverse variance weighted (IVW) method as the main tool for analysis. We utilized statistical data from plasma lipidomics involving 7,174 Finnish individuals and OC data from the FinnGen consortium, including 2,339 European OC patients and 222,078 European healthy controls. Our analysis revealed that elevated levels of four plasma lipids—Phosphatidylcholine (14:0_16:0, O-18:2_18:2, 16:0_20:4)—are linked to an increased risk of OC, while Sphingomyelin (d34:2) seems to act as a protective factor(all P < 0.05). We also conducted tests for heterogeneity and pleiotropy in the MR results. Additionally, reverse MR analysis indicated that OC does not affect plasma levels of these lipids. To determine whether the observed significant plasma lipids influence OC through common risk factors, we selected BMI as a confounder for multivariable Mendelian randomization (MVMR) analysis. The results showed that Sphingomyelin (d34:2) levels remained significantly associated with OC even after including BMI as an exposure factor. Furthermore, we investigated whether these four lipids mediated the effect of BMI on OC but found no evidence supporting their mediating role. In summary, our findings confirm a causal link between certain plasma lipid species and OC, providing fresh perspectives for risk evaluation and potential therapeutic strategies.